Soybean Cyst Nematode Heterodera glycines (Ichinohe, 1952) (Nematoda: Rhabdita: Heteroderidae) - Holly Andres; Zane J. Grabau (EDIS, 2025)
The nematode Heterodera glycines, known as soybean cyst nematode (SCN), is the most economically damaging pest of soybean crops in the United States and around the world. Members of the Heteroderidae family belong in the order Tylenchida; most are plant parasitic while some are insect parasites. They are obligate parasites that attack different species of crops and weeds. Heteroderidae are divided into two groups: cyst and cystoid based on morphological alterations in their skin. The cyst group are unique in that the female skin changes, transforming into a hardened cyst that protects her eggs. Unlike many plant parasites, there may be little to no aboveground evidence of an infestation with H. glycines. They are extremely damaging to the agricultural economy and impossible to eradicate once established, but with proper management, it is possible to minimize H. glycines populations and maximize yield.